Evaluation of Ubi Gajah for bioethanol via hydrolysis and fermentation - Saleh A.A.,; Reddy A.N.R.,; Nadia N.A.,; Charyulu D.K.,; Hamdan S., (Penerbit Universiti Kebangsaan Malaysia, 2019)
This research was carried out to evaluate utilisation of Ubi Gajah (Manihot esculenta), a non-edible cassava species, as a feedstock for bioethanol production by acid hydrolysis. The Ubi Gajah peels and pulp substrates were hydrolysed for a max. of 48 hrs with H2SO4 acid concentration ranges 5% v/v to 15% v/v at high temperature and pressure before fermentation process. While the yield was noted at 24 hr of 15% v/v acid hydrolysis. From the experimental results yield of bioethanol for Ubi Gajah Peel and Pulp 156.65 g/L and 220.89 g/L were noted respectively when both the substrates were hydrolysed with 15% v/v of H2SO4. The FTIR Spectra of the bioethanol, confirms –OH, C-O and C=C groups by absorption bands at 3251.98 cm-1 to 3315.63 cm-1; 1045.42 cm-1 and 1085.92 cm-1; and 1633.71 cm-1 and 1645.28 cm-1 respectively. The biofuel properties were tested according to ASTM standards and found to be complacent. The Bioethanol - diesel blends (BDB) of 5% to 20% v/v were prepared and fuel performance test was conducted on a diesel engine. The performance and emission results confirm suitability of the bioethanol as an alternative fuel.